A Systematic Review of the Impact of Physician Information Sharing on Patient Outcomes - Ismail , Moamen Abdelfadil; ALASSIRI, KHALID MUHAMMED AHMED; albakestani, Meaad yassin; Alzain, Mohannad A; alqahtani , Huda ali mohammed; alrashidy , Reem Ibrahim; ALSADIQI, YOSEF IBRAHIM; Alsubaie , Nawaf Ammash; Alammari , Mohammed Ahmed; Al Zahir , Bayan Ali Ibrahim; hayyan, Manar yahya; Alsulaiman, Layan Mohammed; et al. (Journal of Ecohumanism, 2024)
Background: Effective communication is a cornerstone of high-quality healthcare, empowering patients to make informed decisions, adopt recommended behaviors, and adhere to treatment plans. However, challenges arise due to the complexity of medical information and variations in patient comprehension. This systematic review evaluates the impact of physicians’ information-delivery strategies on patient outcomes, focusing on recall and behavioral changes. Methods: Following PRISMA guidelines, 17 randomized controlled trials (RCTs) were identified from an initial pool of 9,423 abstracts and 175 full-text articles. Studies included interventions using defined communication strategies compared to control conditions, with outcomes measured as patient recall and behavior. Data were synthesized qualitatively due to heterogeneity in intervention methods and outcome measures. Results: The review analyzed 17 RCTs involving 8,256 participants. Information recall improved in 7 out of 10 interventions, with structured delivery and visual aids being particularly effective. Behavioral outcomes showed significant improvements in 8 of 9 studies, driven by strategies like persuasive framing, tailored explanations, and patient-centered approaches. Notable effects included reduced smoking rates, weight loss, and increased treatment adherence. However, the relationship between trust and recall presented nuanced findings. Conclusion: Deliberate communication strategies enhance patient recall and promote health-related behaviors. Structuring information, using visual aids, and applying persuasive techniques yield measurable benefits. Future research should validate these findings in real-world settings, refine cognitive aid strategies, and explore the dynamics of trust and engagement in physician-patient interactions